Lulu's Café [large type] - Lowe, T. I. (Tonya) (Thorndike Press large print clean reads, 2019)
"When a damaged young woman is given a chance to reclaim her life in a small South Carolina town, she must reckon with the dark secrets she left behind in order to accept the love she deserves. On the run from a violent past, Leah Allen arrived in tiny Rivertown, South Carolina, battered and broken, but ready to reinvent herself. By a stroke of fate, Leah is drawn to the Southern hospitality of a small café, looking for a warm meal but finding so much more. Lulu, the owner, offers her a job, a place to stay and a new lease on life. Through Lulu's tenacious warmth and generosity, Leah quickly finds herself embraced by the quaint community as she tries to put herself back together. Given she's accustomed to cruelty, the kindness is overwhelming. Soon Leah meets Crowley Mason, the most eligible bachelor in town. A lawyer and friend of Lulu's, Crowley is wary of Leah's sudden, mysterious arrival. Despite his reserve, something sparks between them that can't be denied. But after all she's been through, can Leah allow herself to truly love and be loved, especially when her first urge is to run? Exploring the resiliency of both the heart and the spirit, Lulu's Café gorgeously illustrates how old scars can finally heal no matter how deep they seem"--